Economic growth in Japan and the USSR - Maddison, Angus (New York : W. W. Norton, 1969)
This publication provides a comparative analysis of the growth experiences of USSR and Japan. It analyses the policies which enables the two countries to transform their economies and to catch up with the developed world. The two countries account for one-fifth of the worlds economy occupying second and third places behind the United States.
Includes index.
Includes bibliographical references: p. 137-141.
lje 18/09/2018
Loans
Keywords: Economic growth; Japan; Soviet Union